The Influence of Working Capital and KUR Credit Provision on UMKM Income Level at PT. Bank Rakyat Indonesia Branch of Bintaro - Hendro Waryanto (Universitas Negeri Makassar, 2020)
Banks develop KUR (Kredit Usaha Rakyat) to improve the competitiveness of the people's small businesses which are expected to have an impact on increasing the income and standard of living of the people towards prosperity. This study aims to determine the effect of working capital and the provision of KUR credit to the level of UMKM income at PT. Bank Rakyat Indonesia Branch of Bintaro. The method used was explanatory research with a sample of 86 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study work capital have a significant effect on UMKM income levels of 20.3%, hypothesis testing obtained significance of 0,000 <0.05. The granting of KUR credit has a significant effect on UMKM income levels of 21.7%, the hypothesis test is obtained at a significance of 0,000 <0.05. Working capital and KUR credit distribution simultaneously had a significant effect on the UMKM income level of 32.9%, the hypothesis test obtained a significance of 0,000 <0.05.